Triose phosphate export from chloroplasts and cellular sugar content regulate anthocyanin biosynthesis during high light acclimation - Max-Emanuel Zirngibl; Galileo Estopare Araguirang; Anastasia Kitashova; Kathrin Jahnke; Tobias Rolka; Christine Kühn; Thomas Nägele; Andreas S. Richter (Plant Communications, 2023)
Plants have evolved multiple strategies to cope with rapid changes in the environment. During high light (HL) acclimation, the biosynthesis of photoprotective flavonoids, such as anthocyanins, is induced. However, the exact nature of the signal and downstream factors for HL induction of flavonoid biosynthesis (FB) is still under debate. Here, we show that carbon fixation in chloroplasts, subsequent export of photosynthates by triose phosphate/phosphate translocator (TPT), and rapid increase in cellular sugar content permit the transcriptional and metabolic activation of anthocyanin biosynthesis during HL acclimation. In combination with genetic and physiological analysis, targeted and whole-transcriptome gene expression studies suggest that reactive oxygen species and phytohormones play only a minor role in rapid HL induction of the anthocyanin branch of FB. In addition to transcripts of FB, sugar-responsive genes showed delayed repression or induction in tpt-2 during HL treatment, and a significant overlap with transcripts regulated by SNF1-related protein kinase 1 (SnRK1) was observed, including a central transcription factor of FB. Analysis of mutants with increased and repressed SnRK1 activity suggests that sugar-induced inactivation of SnRK1 is required for HL-mediated activation of anthocyanin biosynthesis. Our study emphasizes the central role of chloroplasts as sensors for environmental changes as well as the vital function of sugar signaling in plant acclimation.